2014
DOI: 10.1152/ajpheart.00063.2014
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac-restricted overexpression or deletion of tissue inhibitor of matrix metalloproteinase-4: differential effects on left ventricular structure and function following pressure overload-induced hypertrophy

Abstract: MR, Spinale FG. Cardiac-restricted overexpression or deletion of tissue inhibitor of matrix metalloproteinase-4: differential effects on left ventricular structure and function following pressure overload-induced hypertrophy. Am J Physiol Heart Circ Physiol 307: H752-H761, 2014. First published July 3, 2014; doi:10.1152/ajpheart.00063.2014.-Historically, the tissue inhibitors of matrix metalloproteinases (TIMPs) were considered monochromatic in function. However, differential TIMP profiles more recently observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
(88 reference statements)
0
9
0
1
Order By: Relevance
“…Milano et al (170) in a retrospective analysis demonstrated that the 10-yr survival rate was lower in patients with severe fibrosis, calculated from myocardial biopsies obtained during AVR surgery, and there was no significant improvement in NYHA class (170). In both experimental and clinical observations of LV pressure overload, increased TIMPs levels have been identified, which in turn have been postulated to favor a reduction in ECM turnover, contributing to myocardial fibrosis and LV dysfunction (274). In fact, in aortic stenosis, there is an increased production of collagen and a shift towards inhibition of collagen degradation (63,64,98).…”
Section: Myocardial "Reverse Remodeling"mentioning
confidence: 99%
See 1 more Smart Citation
“…Milano et al (170) in a retrospective analysis demonstrated that the 10-yr survival rate was lower in patients with severe fibrosis, calculated from myocardial biopsies obtained during AVR surgery, and there was no significant improvement in NYHA class (170). In both experimental and clinical observations of LV pressure overload, increased TIMPs levels have been identified, which in turn have been postulated to favor a reduction in ECM turnover, contributing to myocardial fibrosis and LV dysfunction (274). In fact, in aortic stenosis, there is an increased production of collagen and a shift towards inhibition of collagen degradation (63,64,98).…”
Section: Myocardial "Reverse Remodeling"mentioning
confidence: 99%
“…Moreover, collagen isoform content suffers alterations during RR with a predominance of collagen isoform I early after debanding that shifts to isoform III a few days later (18). In a mouse model of pressure overload, TIMP-4 overexpression was shown to provide beneficial effects for survival and cardiac function and to mute the fibrotic response, since TIMP-4 overexpression may be beneficial in modulating adverse ECM remodeling in the context of pressure overload (274).…”
Section: Myocardial "Reverse Remodeling"mentioning
confidence: 99%
“…One potential mechanism hypothesized to play a pivotal role in the development of HFpEF is a change in collagen homeostasis that results in extracellular matrix fibrosis and the development of abnormal diastolic function. 812 Several molecular and cellular signaling pathways that result in a profibrotic milieu have been identified in previous studies but have not been specifically examined in randomized clinical trials in HFpEF. 2,6,7 …”
mentioning
confidence: 99%
“…Specifically, we observed a downregulation of Timp4 and upregulation of Timp1. The direction of their opposing trends has been associated with increased collagen content in the setting of LV pressure overload (72). Moreover, we found upregulation of pentraxin-3 (Ptx3), a mediator of innate immunity that has been reported to be correlated with RV mass and end-diastolic volume in patients with PAH (30).…”
Section: Resultsmentioning
confidence: 65%